New International Guidelines and Consensus on the Use of Lung Ultrasound. (22nd August 2022) - Demi, Libertario; Wolfram, Frank; Klersy, Catherine; De Silvestri, Annalisa; Ferretti, Virginia Valeria; Muller, Marie; Miller, Douglas; Feletti, Francesco; Wełnicki, Marcin; Buda, Natalia; Skoczylas, Agnieszka; Pomiecko, Andrzej; et al.
Abstract : Following the innovations and new discoveries of the last 10 years in the field of lung ultrasound (LUS), a multidisciplinary panel of international LUS experts from six countries and from different fields (clinical and technical) reviewed and updated the original international consensus for point‐of‐care LUS, dated 2012. As a result, a total of 20 statements have been produced. Each statement is complemented by guidelines and future developments proposals. The statements are furthermore classified based on their nature as technical (5), clinical (11), educational (3), and safety (1) statements.